Circadian Oscillators: Around the Transcription–Translation Feedback Loop and on to Output. Issue 10 (October 2016) - Hurley, Jennifer M.; Loros, Jennifer J.; Dunlap, Jay C.
Abstract : From cyanobacteria to mammals, organisms have evolved timing mechanisms to adapt to environmental changes in order to optimize survival and improve fitness. To anticipate these regular daily cycles,  many organisms manifest ∼24 h cell-autonomous oscillations that are sustained by transcription–translation-based or post-transcriptional negative-feedback loops that control a wide range of biological processes. With an eye to identifying emerging common themes among cyanobacterial, fungal, and animal clocks,  some major recent developments in the understanding of the mechanisms that regulate these oscillators and their output are discussed. These include roles for antisense transcription, intrinsically disordered proteins, codon bias in clock genes, and a more focused discussion of post-transcriptional and translational regulation as a part of both the oscillator and output. Trends: An apparent lack of structure is a common feature of some of the negative-arm proteins in fungi and animals, and may be essential to their proper function in the circadian clock. The mechanism of circadian period determination does not lie in the half-life of the negative-arm proteins, leaving the potential for alternative methods, such as post-transcriptional regulation, to fill that role. Transcriptional regulation of clock-controlled genes, ccg s, by the heterodimer in the positive arm, once believed to be the absolute driver of changes in expression of ccg s and of output, appears to be just the first step in the pathway of circadian control over cellular output.